Importance of lateral and steric stabilization of polyelectrolyte gene delivery vectors for extended systemic circulation - Oupicky, D; Ogris, M; Howard, K; Dash, P; Ulbrich, K; Seymour, L (Cell Press, 2002)
Gene therapy for systemic diseases requires intravenous administration, but existing vectors are not suitable for systemic delivery, often showing rapid elimination from the bloodstream that restricts potential transfection sites to “first-pass” organs. To develop long-circulating vectors, here we have compared polyplexes containing DNA and poly-L-lysine (PLL) or polyethylenimine (PEI), surface-modified with either monovalent polyethylene glycol (PEG) or multivalent copolymers of N-(2-hydroxypropyl)methacrylamide (PHPMA), correlating their biophysical properties with their distribution following intravenous injection. A key difference between the two types of coating is the introduction of lateral stabilization by surface attachment of multivalent PHPMA, in addition to the steric stabilization provided by both types of polymers. The α-half-life for bloodstream clearance of polycation/DNA polyplexes (typically <5 minutes in mice) could be extended using multivalent PHPMA coating to >90 minutes. We found that the dose administered, as well as the amount and molecular weight of the coating PHPMA, had important effects on circulation properties. Multivalent PHPMA coating allows, for the first time, considerably extended circulation time using polyplex systems—a prerequisite for systemic gene delivery.